High resolution electron exit wave reconstruction from a diffraction pattern using Gaussian basis decomposition - Borisenko, K; Kirkland, A (Institute of Physics Publishing, 2014)
We describe an algorithm to reconstruct the electron exit wave of a weak-phase object from single diffraction pattern. The algorithm uses analytic formulations describing the diffraction intensities through a representation of the object exit wave in a Gaussian basis. The reconstruction is achieved by solving an overdetermined system of non-linear equations using an easily parallelisable global multi-start search with Levenberg-Marquard optimisation and analytic derivatives. © Published under licence by IOP Publishing Ltd.